Influence of mass media on sustainable development goal one attainment in Osun State, Nigeria (2020)
The study’s objective was to examine the influence of mass media on Sustainable Development Goal one attainment in Osun State, Nigeria. Three specific objectives and research questions as well as two hypotheses were enumerated, answered and tested. Simple random sampling technique was employed to select two-hundred and seventy (270) participants from the target popualtion. Descriptive and inferential statistics as well as thematic analysis were used to analysis the data generated from research instruments. The empirical findings revealed that there was awareness through mass media towards various developmental projects installed across the communities under investigation. Besides, the awareness necessitated community stakeholders to give supportive hands to poverty- related projects. Also, it was revealed that awareness through mass media would be a necessary condition but not sufficient one for the attainment of the poverty targets of the Sustainable Development Goal one within the studied araes. In addition, significant gender difference existed towards awareness about implementation and community members’ participation which was in favour of female and male respectively. The study recommended that prominent basic literacy programmes embellished with poverty alleviation information should be disseminated on regular interval, constant mobilisation of the needed physical and financial resources towards implementation of developmental programmes by the concerned stakeholders, regular monitoring and supervision of projects and involvement of the members of community during implementation of poverty alleviation programmes to mention a few